Legal Review of Corruption Crimes in Covid 19 Social Assistance Funds - Adinda Putri Saffanah; Ifahda Pratama Hapsari; Hardian Iskanda (Jurnal Ilmu Hukum, Humaniora dan Politik, 2024)
Weak law enforcement in Indonesia has caused crimes such as corruption of social assistance funds among state officials to increase. Law enforcement is defined as the process of enforcing the norms that apply in Indonesia. Law enforcement is not a fundamental problem, not only because of the complexity of the legal system, the interaction between the legal system and the social, political and economic systems can also be a problem. Corruption has been classified as an extraordinary crime, because it is a criminal offense that has harmed state finances and economic potential. The imposition of criminal penalties or sanctions for perpetrators of criminal acts of corruption has recently been quite less frightening, including in the case of corruption of covid 19 social assistance funds. The writing of this thesis aims to find out the law enforcement against the criminal act of corruption of the covid 19 social assistance fund and the sanctions imposed on the perpetrators of corruption. Sources of legal materials consist of primary materials and secondary materials. The technique of collecting legal materials and data by quoting from data in loose-leaf notes by recording the author's name, book title, publisher's name, year of publication, and page number quoted. Law enforcement against corruption in criminal case decision Number 29/Pid.Sus-TPK/2021/PN Jkt Pst is in accordance with legal norms.